2021
DOI: 10.1016/j.earscirev.2021.103542
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spatial distribution of global 137Cs fallout in soils of South America as a baseline for Earth Science studies

Abstract: Owing to the rapid expansion of agriculture in South America in recent decades, soil erosion and fine 26 sediment supply to river networks, which lead to deleterious on-site and off-site environmental 27 impacts, are exacerbated in intensively cultivated catchments. Measuring soil inventories of bomb-28 derived fallout radiocesium ( 137 Cs) bound to fine particles is one of the few techniques available to reconstruct soil redistribution rates and evaluate the sustainability of farming practices over the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 102 publications
2
3
0
Order By: Relevance
“…In the Cerrado soil, the inventory of 137 Cs is roughly 422 Bq m −2 , which is within the range of values predicted by Chaboche et al. (2021) for this region of Brazil. Since both profiles are only distant by 500 m, we did not interpret the difference in 137 Cs activities as a result in a difference of localized precipitations.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the Cerrado soil, the inventory of 137 Cs is roughly 422 Bq m −2 , which is within the range of values predicted by Chaboche et al. (2021) for this region of Brazil. Since both profiles are only distant by 500 m, we did not interpret the difference in 137 Cs activities as a result in a difference of localized precipitations.…”
Section: Resultssupporting
confidence: 88%
“…Indeed, the 137 Cs activities measured in the Cerrado soil are lower than 1.9 Bq kg −1 , as evidenced for areas located around the Equator, between 20°N and 20°S (e.g., Evrard et al, 2020). In the Cerrado soil, the inventory of 137 Cs is roughly 422 Bq m −2 , which is within the range of values predicted by Chaboche et al (2021) for this region of Brazil. Since both profiles are only distant by 500 m, we did not interpret the difference in 137 Cs activities as a result in a difference of localized precipitations.…”
Section: Anthropogenic Rates Of Erosion Derived From Radionuclide Fal...supporting
confidence: 68%
See 1 more Smart Citation
“…Fallout radionuclide measurements could not be used for the establishment of the core chronology due to the low activities of 210 Pbex and the absence of 137 Cs in the core sediment. Past studies had demonstrated the low 137 Cs activities found in soils and sediment in this low-latitude region of South-America (Chaboche et al, 2021) whereas the 210 Pbex was supposed to be present in the upper part of the soil (≈5cm) before decreasing with depth. The very low lead-210 activities detected in the sediment core can provide information on the intensity of erosion processes in this region by mobilizing subsoil sources (channel bank, gullies) depleted in 210 Pbex, and consequently highly impacted by erosion processes (Evrard et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Most of the existing limnological studies focusing on EN events were consequently focused on marine sediment cores (Hendy et al, 2015). The relative lack of studies can also be explained by the complexity to date these recent sediment archives (>1950) using radionuclides in this this low-latitude area with limited thermonuclear bomb fallout (Chaboche et al, 2021).…”
Section: Introductionmentioning
confidence: 99%